THE PRECARIOUS SYSTEM IN GIG POLITICAL ECONOMY: A STUDY OF THE VULNERABILITY OF ONLINE DRIVERS IN INDONESIA - Nasution, Nanda Rizka Syafriani; Sarah Novianti; Nur Inayah Yushar (Malikussaleh Social and Political Reviews, 2025)
This study is based on the rise of the gig economy in Indonesia, particularly in the online transportation sector, which offers work flexibility but often comes with economic vulnerability for its workers. Online drivers face income uncertainty and a lack of social security, threatening the welfare of their households. This study uses qualitative methods with a literature review and in-depth interviews to examine these issues. The theoretical framework combines the concepts of the precariat, digital political-economic analysis, and human security perspectives to understand the vulnerabilities experienced by workers. The results show that the flexible work system based on digital platforms creates economic uncertainty for online driver workers. This situation is characterized by fluctuating and unguaranteed income, a partnership status that is vulnerable to termination at any time, and very limited social protection. In conclusion, the pseudo-flexibility in this gig economy model creates precarious conditions that undermine the economic security of online drivers and negatively impact their families' welfare. Therefore, structural efforts are needed to improve protection and certainty for workers in Indonesia's gig economy ecosystem.